Measurement and comparison of health utility assessments in chronic rhinosinusitis. Issue 10 (16th June 2015) - Ference, Elisabeth H.; Stubbs, Vanessa; Lidder, Alcina K.; Chandra, Rakesh K.; Conley, David; Avila, Pedro C.; Hirsch, Annemarie G.; Min, Jin‐Young; Shintani Smith, Stephanie; Kern, Robert C.; Tan, Bruce K.
Abstract : Background: Chronic rhinosinusitis (CRS) is a common condition encountered in primary care medicine and is estimated to affect 12.5% of the United States population. This study aims to compare methods of assessing health utility in CRS. Methods: A cross‐sectional sample of CRS patients (n = 137) were interviewed using direct health utility assessment measures: the visual analogue scale (VAS), time trade‐off (TTO), and standard gamble (SG). General quality of life (QOL) scores were obtained via the 36‐item Short Form Health Survey (SF‐36) and converted to SF‐6D health utility values using a Bayesian algorithm. Disease‐specific QOL was measured with the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). A selected subgroup of patients (n = 51) not initiating surgery or new treatment for CRS were re‐interviewed within 3 weeks. Results: The mean ± SD health utilities were VAS 0.69 ± 0.19; TTO 0.80 ± 0.27; SG 0.93 ± 0.11; and SF‐6D 0.72 ± 0.12; they differed significantly ( p < 0.001). Only VAS scores differed based on disease state classification or the presence of nasal polyposis. Correlations between methods of determining health utility were weak, but significant. VAS, TTO, and SF‐6D scores were significantly associated with SNOT‐22 ( p < 0.001 for all); however, SG and SNOT‐22 were poorly correlated (Spearman correlation = −0.33). The test‐retest reliability of TTO (Spearman correlation = 0.71) and SG (0.73) was strong. Conclusion: CRS patients show significant impairment in QOL, with health utility values similar to those of patients with acquired immune deficiency syndrome (AIDS) or intermittent claudication using similar methods. The method of ascertainment significantly affects measured health utility, but the degree of impairment warrants improved recognition and appropriate treatment of the condition.